2008
DOI: 10.1088/1126-6708/2008/01/037
|View full text |Cite
|
Sign up to set email alerts
|

A holographic computation of the central charges ofd= 4, 𝒩 = 2 SCFTs

Abstract: We use the AdS/CFT correspondence to compute the central charges of the d = 4, N = 2 superconformal field theories arising from N D3-branes at singularities in F-theory. These include the conformal theories with E n global symmetries. We compute the central charges a and c related to the conformal anomaly, and also the central charges k associated to the global symmetry in these theories. All of these are related to the coefficients of ChernSimons terms in the dual string theory on AdS 5 . Our computation is e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
164
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(183 citation statements)
references
References 34 publications
(80 reference statements)
19
164
0
Order By: Relevance
“…This gives a check of our formalism. 4. We show that BPS states exist with all primitive charges, i.e.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…This gives a check of our formalism. 4. We show that BPS states exist with all primitive charges, i.e.…”
Section: Discussionmentioning
confidence: 80%
“…for a few highlights see [2,3,4,5,6].) In [7], it was shown that T 3 can be constructed as a theory of class S[A 2 ] (see [8] for more on the definition of class S).…”
Section: Setupmentioning
confidence: 99%
“…When put on T 2 , this is known to reduce to the general-rank version of the E 8 theory of Minahan and Nemeschansky. The central charges a, c and k of these theories were found in [31]:…”
Section: Jhep07(2015)014mentioning
confidence: 99%
“…a D 2 (G) theory [12] (for D 4 AD these two chambers are equivalent). where ∆ is the dimension of the field parametrizing the Coulomb branch of the rank 1 SCFT, and n 7 is the number of parallel 7-branes needed to engineer the SCFT in F -theory [1][2][3][4][5][6][7][8][9]; see Table 1.…”
Section: 2)mentioning
confidence: 99%
“…Consider the seven rank 1 4d N = 2 SCFT's which may be engineered in F -theory using the Kodaira singular fibers [1][2][3][4][5][6][7][8][9] H 0 , H 1 , H 2 , D 4 , E 6 , E 7 , E 8 .…”
Section: Introductionmentioning
confidence: 99%